Adaptasi Penggunaan Teknologi E-Commerce Produk Segar dan Olahan Organik pada Generasi X, Y, dan Z (Studi Kasus Generasi X, Y, dan Z di Kota Bandung dan DKI Jakarta) - Marsyain, Nada Tirtawati; Utami, Hesty Nurul; Setiawan, Iwan (Universitas Galuh, 2024)
Currently, a lot of e-commerce is developing in the field of marketing agricultural products, including fresh and processed organic commodities. This research was conducted to analyze perceived usefulness, perceived ease of use, attitude toward using, and the level of use of e-commerce technology for organic fresh and processed products in generations X, Y, and Z, and then analyze the factors that influence the adaptation to the use of e-commerce technology for organic fresh and processed products in generations X, Y, and Z. In this study a survey method was used by distributing questionnaires to consumers. The results of the study show that perceived usefulness is in the good category, in the opinion of the younger generation, marketing platforms such as e-commerce can be used as a market to meet basic food needs. Perceived ease of use is a good category, illustrating that young people really understand the use of technology in purchasing products. Attitude toward using is categorized as good, illustrating that young people are very receptive to the application of e-commerce technology. The level of technology use is in the good category, it can be concluded that there is a desire to use or reuse e-commerce technology. Characteristics influence and significantly affect attitude toward using and intention to use. Perceived usefulness has no effect on attitude toward using and intention to use. The variable perceived ease of use has a significant effect on attitude toward using and intention to use. While the variable attitude toward using has no effect on intention to use.